The Influence of the Pancasila Student Profile Strengthening Project on the Theme of Sustainable Lifestyle on the Creativity of Fifth Grade Students at SDN Mewek - Kasmiati Kasmiati (UM Purwokerto Press, 2025)
The problem of waste is very often found in our environment. An early age is very necessary. This research aims to examine the influence of the Pancasila Student Profile Enhancement Initiative (P5), focusing on theme of the enduring sustainability lifestyles of the critical reasoning skills of fifth-grade students at SDN Mewek. P5 is an initiative of the Kurikulum Merdeka that emphasizes character education based on Pancasila values, one of theme is instill awareness of sustainable lifestyles through the use af waste in order to foster creativity and attitude of caring for the environment in students. The research approach applied is ex post facto with a quantitive method. The target of population of this study comprises all fifth-grade students, with the data collected through a validated questionnaire. This results identified that there is a significant impact through P5 focusing on the theme of enduring sustainability lifestyles of the critical reasoning skills of students.